Water mist system application in solar collector system to increase clean water production. Issue 10 (10th October 2022) - Sonawan, Hery; Supriyono, Toto; Sofia, Evi; Gani, Ahmad
Abstract: This research is motivated by the problem of lack of clean water in remote areas such as coastal/sea and riverside/estuary areas. Apart from wells, some people also use river water for bathing and washing toilets. Water's low level of hygiene is almost ignored as long as it can still be used to meet daily needs. To overcome this problem, this research proposes a method to convert feed water or brackish water into clean water. The purpose of this study is to investigate an evaporation method to increase clean water production by adding a water mist system to the solar collector. With the discovery of a method to increase clean water production from the purification of feed water, this research makes a small contribution to improving public health, especially communities around the sea coast. This research was carried out using an experimental method referred to as factorial design method. From the experiment, the ratio of clean water production to the feed water flow rate is 7.9%. The maximum clean water production is 5.78ml/minute or 1.25% of the feed water flow rate when using 4 nozzles in the chamber. HIGHLIGHTS: A new evaporation method by water mist system in solar collector system was proposed to increase clean water production.